Tujuan Pembelajaran Islam: Meneliti Ayat-Ayat Dalam Al-Qur'an Dan Manusia Sebagai Objek Pendidikan - Dini Gita Sartika; Lidya Zanti; Riha Datul Aisyah; Merli Anggelia; Wismanto Wismanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Most research on the aims of Islamic education is carried out from the perspective of education as the essence and humans as the subject. However, discussions that study educational objectives from an object perspective still lack information, especially in terms of taking the perspective of several surahs of the Koran. The aim of this research is to describe the aims of education based on verses of the Koran. This research method uses a qualitative method with a library approach, the main information is obtained through books and articles. The research results show that Islamic education is used to teach people about the commands and prohibitions of Allah SWT. over themselves. Thus, the aim of Islamic education is to optimize and empower human reason to act in a good way, not in a wrong way.